Effectiveness of Mobile Technology in Managing Fatigue: Balert App - De La Vega, Ricardo; Anabalón, Héctor; Jara, Cristian; Villamil-Cabello, Eduardo; Chervellino, Miguel; Calvo-Rodríguez, Álvaro (Frontiers in Psychology, 2021)
The performance of professional tasks with a high cognitive, emotional, and even physiological demand, can cause a state of mental fatigue, which implies attentional alterations, greater errors in the tasks performed and a decrease in personal and work productivity caused by a deterioration of the cognitive control processes. The present study presents a mobile phone application named BAlert that allows monitoring and controlling the body's fatigue processes based on the scores obtained in the Stroop effect and the heart rate variability. A pilot study has been carried out with a sample of 63 adults who have used the application a total of 942 times. The results allow us to classify the subjects, by logistic regression analysis, in their fatigue levels in 74% of the occasions. These results highlight the importance of this mobile application to control work fatigue processes in different possible scenarios (military, health, sports, business, etc).